Bandwidth Performance Analysis of a Remote Monitoring Surveillance System - Syed Nor Azlan, Syarifah Ezdiani (2006)
Conventional security surveillance systems require the constant attention of security personnel, to monitor several locations concurrently. With the declining cost of computing power and widespread acceptance of the Internet as a viable communication medium, a low-cost and effective web-based surveillance system becomes an attractive alternative to conventional system.